Immobilization of metallporphyrins on polystyrene: efficient catalysts for aerobic oxidation of alcohols - Naik, R.; Joshi, P.; Deshpande, R. K. (Journal of Molecular Catalysis A-Chemical, 2005)
Metalloporphyrins of iron and cobalt have been successfully encapsulated for the first time using polystyrene matrix, exhibiting high activity for aerobic oxidation of alcohols mimicking cytochrome P-450 dependent mono oxygenases. This communication provides a simple and environmentally friendly protocol for immobilization of metalloporphyrins (MPs) on to polystyrenes in general, which gives stable,I reusable (see Footnote 1) and efficient catalysts for aerobic oxidation of alcohols. These catalysts were characterized by UV-vis as well as diffuse reflectance FT-IR spectroscopy. These catalysts not only have high turnover frequencies but also could be recovered quantitatively by simple filtration and reused without loss of activity. Considering their high dispersing capacity in organic solvents, they will definitely find broad spectrum of applications in the electronic as well as optical fields. This methodology will lead to a potential model to mimic the catalytic action of metalloporphyrins in the niche areas such as catalytic oxidations, drug metabolism, DNA cleavage, photodynamic therapy and many others. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: aerobic oxidation; Immobilization; metalloporphyrins; micro-encapsulation; Polystyrene; turnover frequency

Oxovanadium(IV) complex of 2-(alpha-hydroxyethyl)benzimidazole covalently bonded to chloromethylated polystyrene for oxidation of benzoin - Maurya, Mannar R.; Sikarwar, Sweta; Manikandan, Palanichamy (Applied Catalysis A-General, 2006)
Vanadyl sulphate reacts with 2-(alpha-hydroxyethyl)benzimidazole covalently bonded to chloromethylated polystyrene (PS-Hhebmz) cross-linked with 5% divinyl benzene to give PS-[VO(hebmZ)(2)]. Characterisation of the catalyst was carried out by IR, electronic and EPR spectroscopic studies, thermogravimetry, scanning electron micrographs and elemental analyses. Catalytic potential of the complex was tested for the oxidation of benzoin using tert-butyl hydroperoxide (TBHP) as an oxidant in methanol where benzil, methylbenzoate, benzoic acid and dimethylacetal were obtained as products. Various parameters such as different solvents and concentration of the substrate as well as oxidant have been taken into consideration for the maximum oxidation of the benzoin. Under optimised reaction conditions, a maximum of 98.9% conversion of the benzoin was achieved after 6 h of reaction time where selectivity of the obtained reaction products varied in the order: methylbenzoate (48.5%) > benzil (19.5%) > dimethylacetal (17.1%) > benzoic acid (11.5%). Neat complex was also prepared to compare its catalytic property with polymer-anchored one. EPR spectra of neat and polymer anchored catalyst are characteristics of V(IV) complexes with typical axial pattern and possible square pyramidal geometry. The identical EPR spectral patterns of both freshly prepared and recovered anchored catalysts indicate that the complex is stable and the coordination environment is retained at the end of the catalytic reaction. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: 2-(alpha-hydroxyethyl)benzimidazole; oxidation of benzoin; polymer-anchored complex; Polystyrene; vanadium(IV) complex

New poly(phenylene oxide)/polystyrene blend nanocomposites with clay: intercalation, thermal and mechanical properties - Tiwari, Rajkiran R.; Khilar, Kartic C.; Natarajan, Upendra (Journal of Applied Polymer Science, 2008)
We present the first study and results on the preparation and characterization of montmorillonite clay filter based polymer blend nanocomposites of the miscible poly(phenylene oxide)/polystyrene blend. Intercalated nanocomposites, prepared by a melt-processing method with 2-6 wt % commercially available organically modified sodium montmorillonite, have been characterized with wide-angle X-ray diffraction, transmission electron microscopy analysis, thermal analysis (thermogravimetric analysis and differential scanning calorimetry), and mechanical tensile tests. We show that nanocomposites can be successfully prepared in a batch mixer at temperatures much below the conditions conventionally used for this blend without organic degradation. Thermal stability is enhanced by nanoscale hybrid formation. The level of intercalation (change in the d-spacing) does not change with the clay loading. Better dispersion of clay in the blend matrix has been observed at a low level of clay content. The nanocomposites show improved tensile modulus (by 31%) in comparison to the blend, whereas the tensile strength (stress at break) and elongation decrease in the presence of the filler with an increase in the clay loading. The Halpin-Tsai model is able to predict the modulus of the nanocomposites in very good agreement with the experimental data. (c) 2008 Wiley Periodicals, Inc.
Keywords: mechanical properties; Nanocomposites; organoclay; poly(phenylene oxide); Polystyrene; Thermal properties

Effect of composition on chain dimensions of styrene-methylmethacrylate random copolymers under theta condition - Karyappa, Rahul B.; Natarajan, Upendra (Journal of Macromolecular Science Part B-Physics, 2011)
Rotational-isomeric-state (RIS)-Metropolis Monte Carlo simulations are performed on poly(styrene-ran-methylmethacrylate) random copolymers to study the intrinsic unperturbed (theta-condition) dimensions. Mean-squared end-to-end distance (< r(2)>(o)), mean-squared radius of gyration (< s(2)>(o)), and characteristic ratio (C(n)) have been calculated for these copolymers constituted by different overall chemical compositions (styrene fractions 0.29, 0.56, and 0.70). Calculations were carried out with chains of 500 repeating units. With an increase in the styrene content there is an increase in (< r(2)>(o)), `, and C(n), in agreement with experimental observations. An increase in the fraction of trans conformational states in the backbone torsion angles is found to be responsible for the exhibited chain expansion behavior. The dimensions calculated by the Monte Carlo simulations agree well with experimental values reported in the literature.
Keywords: chain dimensions; Monte Carlo; poly(methyl methacrylate); Polystyrene; random copolymer; theta conditions

Studies on the feasibility of recycled polystyrene doped with NLO active meta-Nitroaniline for optoelectronics applications - Sureshkumar, M. S.; Goyal, R. K.; Negi, Y. S.; Pratheepkumar, A.; Reddy, K. Raghunatha; Singh, R. P.; Dadge, Jagdish W.; Aiyer, Rohini C. (Polymers for Advanced Technologies, 2011)
A Guest-Host system based on meta-Nitroaniline (m-NA) and recycled polystyrene (RPS) susceptible to generate nonlinear optically (NLO) active property such as second harmonic generation (SHG) has been prepared. Pure, sublimed, optical grade, crystalline m-NA is used as a guest and RPS from the disposable packaging waste as available utilized as the host polymer. In this paper we report the effect of NLO active m-NA on the bulk and optical properties of RPS. The purified m-NA was incorporated from 1-10 wt% in the RPS polymer matrix by conventional solution casting method. Thin, transparent, freestanding films obtained were characterized with optical microscope, scanning electron microscope (SEM), viscosity measurement, and UV-Visible (UV-Vis) spectroscopy for bulk properties evaluation and Nd:YAG laser studies for optoelectronics application such as SHG through frequency doubling. Copyright (C) 2010 John Wiley & Sons, Ltd.
Keywords: frequency doubling; guest-host NLO systems; meta-Nitroaniline; nonlinear optical activity; Polystyrene; second harmonic generation

Synthesis of bis-allyloxy functionalized polystyrene and poly (methyl methacrylate) macromonomers using a new ATRP initiator - Sane, Prakash S.; Palaskar, Dnyaneshwar V.; Wadgaonkar, Prakash P. (European Polymer Journal, 2011)
A new bis-allyloxy functionalized ATRP initiator, viz, 4,4-bis (4-(allyloxy) phenyl) penty1-2-bromo-2-methylpropanoate was synthesized starting from commercially available 4,4-bis (4-hydroxyphenyl) pentanoic acid. Atom transfer radical polymerization of styrene in bulk and that of methyl methacrylate in anisole using CuBr/N,N,N',N',N `'-pentamethyldiethyl-enetriamine system was carried out. The kinetic study of styrene polymerization showed controlled polymerization behavior. Bis-allyloxy functionalized well-defined polystyrene (M(n)(GPC): 13,600-28,250, PDI: 1.07-1.09) and poly (methyl methacrylate) (M(n)(GPC): 10,100-18,450, PDI: 1.23-1.34) macromonomers were obtained. The presence of allyloxy functionality was confirmed by (1)H NMR spectroscopy. The reactivity of allyloxy functionality was demonstrated by carrying out organic reactions such as addition of bromine and hydrosilylation on polystyrene macromonomer. Polystyrene macromonomer with bis-allyloxy functionality was transformed into bis-epoxy functionalized polystyrene macromonomer using 3-chloroperoxybenzoic acid. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Allyloxy end-functional polymer; Atom transfer radical polymerization (ATRP); Macromonomers; Poly (methyl methacrylate); Polystyrene

Aromatic aldehyde functionalized polycaprolactone and polystyrene macromonomers: synthesis, characterization and aldehyde-aminooxy click reaction - Sane, Prakash S.; Tawade, Bhausaheb V.; Palaskar, Dnyaneshwar V.; Menon, Shamal K.; Wadgaonkar, Prakash P. (Reactive & Functional Polymers, 2012)
New bis-aldehyde functionalized initiators, viz, 4,4'-(4,4'-(5-hydroxypentane-2,2-diyl)bis(4,1-phenylene))bis(oxy)dibenza ldehyde (1) and 4,4'-bis(4-(4-(formylphenoxy) phenyl) pentyl 2-bromopropanoate (2) were synthesized starting from commercially available 4,4'-bis(4-hydroxyphenyl) pentanoic acid. These initiators were utilized, respectively, for ring opening polymerization of E-caprolactone and atom transfer radical polymerization of styrene. Well-defined polycaprolactone macromonomers (M-n(GPC): 2600-19400, PDI: 1.37-1.47) and polystyrene macromonomers (M-n(GPC): 2800-28200, PDI: 1.11-1.16) with bis-aldehyde functionality were synthesized. The kinetic study of styrene polymerization showed controlled polymerization behaviour. The presence of aldehyde functionality in macromonomers was confirmed by H-1 NMR spectroscopy. The reactivity of aldehyde functionality was demonstrated by carrying out aldehyde-aminooxy click reaction of polycaprolactone macromonomer with O-(2-azidoethyl) hydroxylamine which proceeded in a quantitative manner without backbone degradation. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Aldehyde-terminated macromonomers; ATRP; Polycaprolactone; Polystyrene; ROP

Impact of plasticizer addition on molecular properties of polybutadiene rubber and its manifestations to glass transition temperature - Sharma, Pragati; Roy, Sudip; Karimi-Varzaneh, Hossein Ali (Macromolecular Theory and Simulations, 2019)
Effect of blending low and high T-g polymer on the structural, spatial, and temporal properties of the polybutadiene rubber are investigated using molecular dynamics simulations. It is elucidated that smaller chain length counterpart of polybutadiene (5mer-OB) acts as plasticizer for the polybutadiene rubber matrix (32mer-PB). Observed flexibility at macroscopic level by plasticizer addition is corroborated at the molecular level in the form of lower conformational rigidity and faster diffusion of polybutadiene chains in the mixtures. It is inferred that plasticizers decreases T-g of the matrix, due to cooperative influence of decreased chain packing and rigidity. Opposite effect is observed in mixtures with high T-g polymer, polystyrene. T-g of the mixtures showed substantial dependence on the type, concentration, chain length as well as miscibility of plasticizers in the matrix. However, the effect of increasing chain length is more pronounced but counter-controlled by the spatially heterogeneous distribution of the plasticizer. Clustering of polystyrene chains induced significant dynamic heterogeneity in the homogeneous polybutadiene matrix, which apparently lead to reduced plasticization effect. Addition of plasticizers in rubber induce discernible changes in the structural and dynamic properties of the rubber matrix, which manifest as the variation in glass transition and explains the real-life activity of plasticizers.
Keywords: Glass transition temperature; MD Simulation; plasticizer action; polybutadiene rubber; Polystyrene; spatial and dynamic heterogeneity

Novel biosurfactant assisted biodegradation of polystyrene by Actinomycetes and its chemical understanding - Sakpal, Amrapali; Haq, Nazrul; Dasgupta, Santanu; Alanazi, Fars; Alsarra, Ibrahim A.; Alam, Mahboob; Dastager, Syed G. (Polymer Degradation and Stability, 2026)
The current study highlights the effective biodegradation of polystyrene by two actinobacterial strains, Glutamicibacter sp. K-1 and Rhodococcus sp. BG-30. FT-IR, Raman spectroscopy, and GPC data showed the degradation pattern of polystyrene. Additionally, GC-MS analysis showed that strain K-1 produced a variety of degradation by-products, including alkanes, 2,4-Di-ter-butyl phenol, 2-propenoic acid, tridecyl ester, and dibutyl phthalate, while strain BG-30 produced a greater amount of alkenes, phthalic acid, and isobutyl octyl esters. GPC detected a drop in polystyrene's average molecular weight (Mn), which suggests chain scission of the polymer. Changes in polystyrene's roughness and other morphological properties were shown by AFM and FE-SEM. The effects of a conventional rhamnolipid and a novel thermostable biosurfactant fatty alkene (0.1 % each) on the breakdown of polystyrene were examined. Strain K-1 and BG-30 resulted in increasing the degradation of polystyrene to 12 % (w/w) and 16 % (w/w), respectively in the presence of fatty alkene biosurfactant, there was 10 % (w/w) and 8 % (w/w), degradation in presence of rhamnolipid. To the best of our knowledge, degradation of polystyrene by Glutamicibacter sp. has been reported as a newly identified strain and use of a novel biosurfactant together revealed their potential in biodegradation of plastic to mitigate the plastic pollution using microbial resources.
Keywords: Biodegradation; Fatty alkene biosurfactant; Glutamicibacter sp.; Polystyrene; Rhamnolipid; Rhodococcus sp.